Global Cities and Sustainable Development Goals: How do places of decoupling and exploitation become places of social inclusion? - Denk, Albert (Momentum Quarterly, 2019)
The concept of the global city describes a process of decoupling between cities and their territorial states. Global cities act in a kind of city network that operates by its economic activities, almost detached from state interventions. In addition, processes of exploitation of natural resources and transnational workforce, which further strengthen decoupling, are taking place. By means of the United Nations’ Sustainable Development Goals (SDGs) an agenda was created that seeks to develop sustainable cities from the social inclusion perspective. This contribution shows, through the example of global cities, how the territorial-state-oriented SDGs are limited with special reference to transnational processes, globally operating labor and global migration movements. In the process, Development Goal #11 will be scrutinized and the following questions will be investigated: How can processes of social inclusion be strengthened in global cities? And what potential lies in the United Nations’ Sustainable Development Goals?